2020
DOI: 10.1007/s00464-020-07719-w
|View full text |Cite
|
Sign up to set email alerts
|

Low-pressure pneumoperitoneum with deep neuromuscular blockade in metabolic surgery to reduce postoperative pain: a randomized pilot trial

Abstract: Background For metabolic laparoscopic surgery, higher pressures up to 20 mmHg are often used to create a surgical field of sufficient quality. This randomized pilot study aimed to determine the feasibility, safety and tolerability of low intraabdominal pressure (IAP) and deep neuromuscular blockade (NMB) to reduce postoperative pain. Methods In a teaching hospital in the Netherlands, 62 patients eligible for a laparoscopic Roux-en-Y gastric bypass (LRYGB) were randomized into one of four groups in a 2 × 2 fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…In evaluating the need for muscle relaxants for optimal surgical conditions, 26 randomised clinical trials were included 45–70 . We considered studies that investigated deep (dNMB) vs. moderate (mNMB) or no neuromuscular block in the adult population.…”
Section: Evidence Summary and Commentmentioning
confidence: 99%
“…In evaluating the need for muscle relaxants for optimal surgical conditions, 26 randomised clinical trials were included 45–70 . We considered studies that investigated deep (dNMB) vs. moderate (mNMB) or no neuromuscular block in the adult population.…”
Section: Evidence Summary and Commentmentioning
confidence: 99%
“…[5][6][7] While other studies have shown no difference between pain scores using low pressure pneumoperitoneum. [9][10][11][12][13] Because the nurses at our hospital only have to document pain scores if they are going to administer pain medications, our study had much fewer nurse recorded pain scores at discharge than the number of patients with recorded MME. Therefore, we postulate, the lack of significance of nurse recorded pain scale in our study could be attributed to the smaller data set of pain scores and thus result in a type 2 error.…”
Section: Discussionmentioning
confidence: 99%
“…One study of low pressure pneumoperitoneum found the need to increase to standard pressure from low pressure in a large percentage of patients undergoing bariatric surgery. 11 Due to the operative challenges that come with bariatric patients, a study assessing the usage low pressure usage could be further explored in this specific subset of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations